2012
DOI: 10.3402/gha.v5i0.14876
|View full text |Cite
|
Sign up to set email alerts
|

Community-based blood pressure measurement by non-health workers using electronic devices: a validation study

Abstract: IntroductionPopulation monitoring and screening of blood pressure is an important part of any population health strategy. Qualified health workers are expensive and often unavailable for screening. Non-health workers with electronic blood pressure monitors are increasingly used in community-based research. This approach is unvalidated. In a poor, urban community we compared blood pressure measurements taken by non-health workers using electronic devices against qualified health workers using mercury sphygmoman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The study reported here supports contemporary policy commitments to the value of CHWs, demonstrating the work they do in integrating health and welfare initiatives in low-income, CTC settings, confirming the conclusions drawn in previous, initiative-specific studies [e.g. ( 1 , 2 )]. However, there was no evidence here of Lehmann & Sanders’ differentiation ( 5 ) between generalists and specialists; all CHWs involved here could be seen as generalists, who acted as specialists in response to specific funded programmes, but whose role extended beyond this, providing continuity for the community whilst funding comes and goes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The study reported here supports contemporary policy commitments to the value of CHWs, demonstrating the work they do in integrating health and welfare initiatives in low-income, CTC settings, confirming the conclusions drawn in previous, initiative-specific studies [e.g. ( 1 , 2 )]. However, there was no evidence here of Lehmann & Sanders’ differentiation ( 5 ) between generalists and specialists; all CHWs involved here could be seen as generalists, who acted as specialists in response to specific funded programmes, but whose role extended beyond this, providing continuity for the community whilst funding comes and goes.…”
Section: Discussionsupporting
confidence: 88%
“…Community engagement in health systems has been seen as both a practical response to the challenging conditions of health provision in low-income settings [e.g. ( 1 , 2 )] and a key principle for strengthening health systems more generally ( 3 ). However, a substantive account of CHW's own view of their own practice has been lacking up until now, hindering the integration or alignment of CHWs to the formal health care system at the community level.…”
mentioning
confidence: 99%
“…Adams et al ( 17 ) demonstrated health volunteers without a professional health worker background could be trained to make accurate blood pressure and anthropometric measurements. Reidpath et al found that blood pressure readings made by non-health workers were not statistically different from those made by health workers ( 18 ). A study showed that in India, CHWs could be trained to calibrate blood pressure apparatus in the local setting, and that CHWs made similar BP measurements as their educated supervisors ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure was measured at rest with an interval of 2 min between readings (Omron model HEM-7203) based on a validated strategy for community-based measurement (Reidpath et al 2012). The three blood pressure measures were averaged and used to categorise diastolic and systolic blood pressure (mmHg) according to the following cutoffs: normotensive (systolic \ 120 and diastolic \ 80; reference category), pre-hypertensive (120 C systolic \ 140; 80 C diastolic \ 90), hypertensive (140 C systolic; 90 C diastolic).…”
Section: Methodsmentioning
confidence: 99%